Development of High Chromium White Cast Iron Liquefaction Technology - Saidmakhamadov Nosir; Karimov Bokhodir; Hudoykulov Shohruh; Bekjanova Laylo (Genius Journals, 2022)
In this paper, high-chromium 280X29NL cast iron is reduced to 28.86 – 31% to 14 – 15%, 1% gchach Cu is added, the chemical composition is changed and the new brand 280X15TDL alloy is economically cheap and brittle, without reducing the mechanical properties of the alloy 0.4 was liquefied in an induction furnace. For thermal treatment of the alloy, they were heated to a certain temperature by SNOL – 7.2 / 1100 muffle furnace and cooled in air after standing for a certain time at a temperature of 8500 C. In this process, the chemical composition of the alloy did not change, but its properties changed due to changes in its structure.
Keywords: Copper; induction furnace; muffle furnace; microstructure